ANALISIS TRADING VOLUME ACTIVITY DAN AVERAGE ABNORMAL RETURN SEBELUM DAN SESUDAH MELAKUKAN PEMECAHAN SAHAM (STOCK SPLIT) PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA. - Anita Tri Utami (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2017)
This research is titled “Analysis of Trading volume activity and Average Abnormal Return beforeand after the stock split pada companies listed on the bursa efek indonesia” . this researchaims to analysing is there any differences between the abnormal return and the trading volumeactivity before and after the stock split. The data that have been used in this research are thedaily stock price and the IHSG of the companies who did the stock split in 2011 till 2015.Bythe purposive sampling methods, there is 32 companies who did the stock split that listed onthe bursa efek indonesia. Analysis technique that has been used is Uji normalitas dan uji bedadua sampel berhubungan uji wilcoxon with the event window is 5 days before and 5 days afterthe stock split.The result of this research is show that there is 0,024 < 0,05 significant valuefrom the Pengujian Uji Beda between trading volume activity before and trading volume activityafter stock split. Based on that fact, there is 0,033 < 0,05 significant value from pengujian ujibeda between abnormal return before and bid-ask spread after the stock split. Thus can beinterpreted that there is a difference between abnormal return before and after stock split. Sothat the Indonesia Capital market is yet efficient and yet strong enough by the stock split.Keywords: Stock split, Abnormal Return, Trading volume activity.